STUDENTS’ CRITICAL THINKING ABILITY IN ENGLISH TEACHING AND LEARNING - Tini Mogea (Jurnal Pendidikan dan Sastra Inggris, 2022)
The purpose of this study was to discover how students' critical thinking skills developed during the classroom learning process. This research was conducted at SMA Negeri 1 Ratahan, and the sample is the first-year students, which was made up of 35 students. The instruments used in collecting data are observation techniques. The data were analyzed qualitatively. 1) The concept of purpose was present in Meetings 2, 3, 4, and 5. It is shown that when students reason, they reason to achieve some objective, to satisfy some desire, or to fulfill some need. 2) The concept of "question" was in Meetings 1, 2, 4, and 5. This shows that generally, the students had questions and problems to be solved. (3) The concept of concept was only observed in Meetings 2, 3, and 5. Some ideas or concepts are used in all reasoning but not others. 4) The concept of assumption was in Meetings 1, 2, 4, and 5. All reasoning must begin somewhere; we must take some things for granted. Any "defect" in the assumptions or presuppositions with which the reasoning begins is a possible source of problems for students. 5) Only at Meeting 5 was the concept of information discussed. Whenever we reason, there is some "stuff," some phenomenon, about which we are reasoning. Any "defect," then, in the experiences, data, evidence, or raw material upon which a person’s reasoning is based is a possible source of problems. 6) The concept of interpretation was discussed in Meetings 3 and 4. Reasoning proceeds in steps: "Because this is so, that also is so (or probably so)," or "Since this, therefore that." Any "defect" in such inferences is a possible problem in our reasoning. 7) In Meetings 3 and 5, the concept of point of view or frame of reference was discussed. In this case, students reason within certain frames of reference. Any "defect" in that point of view or frame of reference is a possible source of problems in the reasoning. 8) Only Meetings 3 and 4 discussed the concept of implications (and consequences). Any "defect" in the implications or consequences of our reasoning is a possible source of problems.